Visitor Satisfaction at PAS TJ Grape Plantation Agrotourism in Singkawang - Suprianti, Riya; Dolorosa, Eva; Suharyani, Anita (Business Review and Case Studies, 2025)
Background: PAS TJ Grape Plantation Agrotourism analyses visitor satisfaction to improve services and attract more visitors.Purpose: This research analyses visitor satisfaction levels at PAS TJ Grape Plantation Agrotourism in Singkawang. By utilising the 7A+1S framework (attraction, amenities, Ancillary services, activity, accessibility, available package, accommodation, and sustainability), this research evaluates the factors influencing visitor experiences. The findings are expected to provide recommendations for managers to enhance service quality and the attractiveness of agrotourism, thereby supporting sustainable agrotourism.Design/methodology/approach: This research employs a nonprobability sampling method with a purposive sampling technique on 40 respondents. Data were collected through structured questionnaires and analysed using descriptive statistical methods. Validity and reliability tests were conducted, along with the Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA), to assess visitor satisfaction and service performance.Findings/result: Based on the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA), visitor satisfaction at PAS TJ Grape Plantation reached 81.22%, categorised as "very satisfied." While visitors generally have a positive experience, some aspects need improvement. The IPA results highlight the availability of a canteen, road conditions, and supporting infrastructure as key concerns, as they are essential but underperforming. Meanwhile, other attributes meet or exceed expectations. Addressing these gaps, particularly those in Quadrant I (high importance, low performance), is crucial for enhancing visitor satisfaction.Conclusion: Overall, the attributes of PAS TJ Grape Plantation agrotourism in Singkawang are very satisfying for visitors. However, improvements in facilities and infrastructure are needed to enhance visitor satisfaction and attract more visitors in the future.Originality/value (State of the art): This research contributes to developing a visitor satisfaction analysis methodology by applying the 7A+1S approach, which has not been widely used in agritourism. Focusing on PAS TJ Grape Plantation Agrotourism, this research is expected to serve as a reference for developing sustainable agritourism in other regions.Keywords: Visitor satisfaction, Agrotourism, Customer satisfaction index (CSI), and Importance performance analysis (IPA)